Factors determining uncertainty in capital budgeting decision making: Perspectives on Sri Lankan Listed Companies - Kengatharan, L. (My University, 2017)
Allocating resources among competing investment projects is one of the most critical decisions made by the top management and is of strategic importance, and it invariably involve large sums of money and have a long-term economic life cycle. These decisions are critical to managing strategic change and sustaining long term corporate performance. Current investment markets are evolving within an increasingly volatile and intertwined global network and investments are strongly exposed to uncertainties .Uncertainties could lead to failure of a good investment decision and thus integration of uncertainty with capital budgeting techniques is overarching, nonetheless, often complex . Over the last two decades, corporate practices regarding capital budgeting have not been static and have diverged from theories. Therefore, aim of this study was to identify the factors indicating uncertainty in capital budgeting decision making which focused on Sri Lankan listed companies .The data for this study were garnered from 186 CFOs working in companies listed on the Colombo Stock Exchange using selfadministered questionnaires. The questionnaire was piloted with a sample of five CFOs. After the data were collected, they were analysed using multivariate analysis such as factor analysis and confirmatory factor analysis. This study identified four major types of specific uncertainty factors: market uncertainty (uncertainties on competitive, output market and input market), social uncertainty (uncertainties on policy, political and social), operational uncertainty (uncertainties on input, labour and production) and financial uncertainty (uncertainties on interest rate, inflation rate and exchange rates). Overall, this study has made parametric contributions as identified four uncertainty factors ,beyond its valuable contribution, this study serves as a springboard for future research.
Keywords: Market Uncertainty; Social Uncertainty; Operational Uncertainty; Financial Uncertainty